Searching for the pioneers’ sites and beyond. Archaeological surveys at Santiago del Estero plain (Argentina) and their contributions to the regional research issues - Taboada, Constanza (2021)
This paper presents the results of surveys carried out in the south center of Santiago del Estero plain (Argentina), which revealed 12 archaeological sites. Most of them could be related to those mentioned in the pioneer archaeological researches in the region, whose identity and localization were currently unknown. Characteristics, alteration factors, material diversity, distribution, and possible chronological and cultural implications are described for each site. Evidence from some sites that exhibit a material pattern different from that of the regional Late Period is highlighted because it could contribute to the discussion of a possible settlement since the first millennium AD, unknown in the region until now. This issue needs to be addressed with new excavations and modern dating techniques.